Structure of tandem RNA recognition motifs from polypyrimidine tract binding protein reveals novel features of the RRM fold - Conte, Maria R. (Oxford University Press, 2000)
Polypyrimidine tract binding protein (PTB), an RNA binding protein containing four RNA recognition motifs (RRMs), is involved in both pre-mRNA splicing and translation initiation directed by picornaviral internal ribosome entry sites. Sequence comparisons previously indicated that PTB is a non-canonical RRM protein. The solution structure of a PTB fragment containing RRMs 3 and 4 shows that the protein consists of two domains connected by a long, flexible linker. The two domains tumble independently in solution, having no fixed relative orientation. In addition to the βαββαβ topology, which is characteristic of RRM domains, the C-terminal extension of PTB RRM-3 incorporates an unanticipated fifth β-strand, which extends the RNA binding surface. The long, disordered polypeptide connecting β4 and β5 in RRM-3 is poised above the RNA binding surface and is likely to contribute to RNA recognition. Mutational analyses show that both RRM-3 and RRM-4 contribute to RNA binding specificity and that, despite its unusual sequence, PTB binds RNA in a manner akin to that of other RRM proteins.